2015
DOI: 10.1038/ijo.2015.186
|View full text |Cite
|
Sign up to set email alerts
|

Is grand-parental smoking associated with adolescent obesity? A three-generational study

Abstract: Background/Objectives Data from previous studies consistently suggest that maternal smoking is positively associated with obesity later in life. Whether this association persists across generations is unknown. We examined whether grand-parental smoking was positively associated with overweight status in adolescence. Subject/Methods Participants were grandmother-mother-child triads in the Nurses’ Health Study II (NHS II), the Nurses Mothers’ Cohort Study, and the Growing up Today Study (GUTS). Grandmothers pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…The authors also posit that because, in some studies, control for generation 2 covariates leads to grandmaternal smoking being associated with higher grandchild birth weight, controlling is incorrect. However, if grandmaternal smoking lowers maternal birth weight, which in turn is associated with a higher metabolic risk, an increase in grandchild weight would be consistent with the hypothesized pathway . As always, the correct analysis depends on the research question.…”
mentioning
confidence: 99%
“…The authors also posit that because, in some studies, control for generation 2 covariates leads to grandmaternal smoking being associated with higher grandchild birth weight, controlling is incorrect. However, if grandmaternal smoking lowers maternal birth weight, which in turn is associated with a higher metabolic risk, an increase in grandchild weight would be consistent with the hypothesized pathway . As always, the correct analysis depends on the research question.…”
mentioning
confidence: 99%
“…However, these findings do not agree with the study results of Carslake et al (2016) [59] which found no clear association between paternal early-onset smoking (before the age of 11) and higher BMI values in offspring [59]. Instead, another study by Dougan et al (2016) [60] could show that grand-paternal smoking during pregnancy of the grandmother was associated with a higher risk for granddaughters at the age of 12 to be overweight or obese. A link between grand-paternal smoking and the BMI of the grandson was not established [60].…”
Section: Paternal Risk Factors: Epidemiological and Clinical Studiesmentioning
confidence: 60%
“…Instead, another study by Dougan et al (2016) [60] could show that grand-paternal smoking during pregnancy of the grandmother was associated with a higher risk for granddaughters at the age of 12 to be overweight or obese. A link between grand-paternal smoking and the BMI of the grandson was not established [60]. Deng et al (2013) [61] and Cresci et al (2011) [62] reported that paternal smoking was associated with conotruncal heart defects.…”
Section: Paternal Risk Factors: Epidemiological and Clinical Studiesmentioning
confidence: 95%
“…Transgenerational studies in humans that are focused on children's birthweight 19 and weight status [29][30][31][32][33][34][35][36] have examined the influence of grandparental obesity, [30][31][32] diabetes, 29,36 smoking, [33][34][35] and elevated cardiometabolic risk. 19 The available evidence, however, is limited by small sample sizes, 19,30,36 self-report of information, [29][30][31][32][33] the inability to adjust for all relevant confounders, 31 and improper adjustment for mediators. 19,29,[34][35][36] Thus, the need to clarify these transgenerational associations remains.…”
Section: Backg Rou N Dmentioning
confidence: 99%